Peningkatan Hasil Belajar melalui Model Group Investigation Berbantuan Media Poster pada Siswa Sekolah Dasar - Astuti, Risti Tri; Kanzunnudin, Moh; Ardianti, Sekar Dwi (EduBasic Journal: Jurnal Pendidikan Dasar, 2020)
This research is based on the reality that in State Elementary School 03 of Sukoharjo, learning was carried out in the method for all lesson. It made students to be passive in learning thus resulting poor learning outcome.This study aimed to describe the improvement of student learning outcome with group investigation model assisted by poster in theme 6 â€œHeat and its Transferâ€ in fifth grade of State Elementary School 03 of Sukoharjo. This study was classroom action research which was conducted in Â a number of 14 students. This research was conducted in two cycles where each cycles consisted of four stages of planning, implementation, observations, and reflection. Data collection was obtained through test, observation, interview and documentation. The data was analysed quantitatively and qualitatively The result showed an increase in students learning outcomes in aspects of knowledge, attitude, and skills. Studentsâ€™ learning outcome in aspect of knowledge have increased from 71,42% in the cycle I to be 92,85% in cycle II. In aspect of attitude, students, learning outcome have also increased in cycle I by 71,42% to be 89,28% in cycle II. Studentsâ€™ learning outcome also increased in aspect of skills by 74,99% in the cycle I to be 89,28% in cycle II. The results indicated that the use of Group Investigation with Poster media can improve the studentsâ€™ learning outcome in knowledge, attitude and skill aspects in elementary school level.